Paradigma Positivistik Comte sebagai Kerangka Analisis Realitas Sosial Masa Kini - Sihono, Ridwan Faqih; Usman (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2025)
This study examines the relevance of Auguste Comte’s positivist paradigm in interpreting contemporary social realities characterized by technological acceleration, complex social interactions, and the growing dominance of data-driven systems. Positivism, grounded in empirical observation, verification, and the search for social laws, continues to offer a structured analytical framework for identifying patterns and regularities within modern society. However, rapidly changing social conditions reveal that many aspects of human life contain subjective, cultural, and symbolic dimensions that cannot be fully reduced to quantitative variables. Therefore, this study argues for the expansion of positivism through post-positivist and mixed-methods approaches capable of integrating empirical precision with interpretive depth. The findings affirm that positivism remains relevant as an analytical foundation, but it becomes truly effective only when used in dialogue with qualitative and critical perspectives to produce more comprehensive and context sensitive understandings of social phenomena.